A Systematic Review of Ecological Impact Assessment Methodologies, Circular Economy Integration, and Geotechnical Solutions for Minimizing Resource Extraction Footprints - Anitha, Latha Abel (Journal of Progress in Civil Engineering, 2025)
The mining industry is very important for the economy around the world because it supplies key materials. Yet, it faces big environmental and social issues that require attention to sustainable methods. This paper, called Sustainable Mining Practices and Environmental Geology, gives a detailed look at current techniques and their effects on resource extraction and environmental care. It looks closely at new ideas created to meet the high needs of mineral production while also working to reduce harm to nature. By considering various aspects like new technologies, laws, and how much communities are involved, the paper aims to find the best ways to ensure both resource use and fairness in society as well as care for the environment. Through thorough examination, this study highlights the pressing need for the mining industry to use sustainable methods that match global sustainability goals. It raises key questions about how well current policies and methods are working and ultimately calls for a shift towards responsible resource management that responds to the increasing environmental challenges we face today.